(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
Metabolic syndrome, defined by the co-occurrence of central obesity, insulin resistance, dyslipidemia, and hypertension, represents one of the most prevalent and clinically consequential conditions of the twenty-first century, affecting over one billion individuals globally and conferring dramatically elevated risk of type 2 diabetes, cardiovascular disease, non-alcoholic fatty liver disease, and certain malignancies. Mounting evidence positions chronic low-grade inflammation and immune dysregulation as central mechanistic drivers of metabolic syndrome pathogenesis, linking adipose tissue dysfunction, gut microbiome alterations, and innate immune activation in a self-reinforcing cycle of metabolic deterioration. This review synthesizes current understanding of the immunological underpinnings of metabolic syndrome, examining the roles of pro-inflammatory adipokines, macrophage polarization, inflammasome activation, and adaptive immune dysregulation in disease progression. The contributions of visceral adipose tissue as an immunologically active organ, the gut microbiome as a modulator of systemic inflammation, and epigenetic regulation of inflammatory gene networks are examined in depth. Emerging biomarkers of inflammo-metabolic risk, including interleukin-6, tumor necrosis factor-alpha, C-reactive protein, and novel adipokine panels, are discussed in the context of clinical risk stratification. Therapeutic strategies targeting the inflammatory axis of metabolic syndrome, including lifestyle interventions, anti-inflammatory pharmacotherapy, GLP-1 receptor agonists, and microbiome-modulating approaches, are evaluated against current evidence. This review underscores the imperative of integrating immunological profiling into metabolic syndrome management and highlights unresolved questions for future translational research.